Influencia de hongos endomicorrízicos en el crecimiento de (Tabebuia donnell-smithii Rose) - Aguirre Medina, Juan Francisco; Yeekón-Méndez, Lázaro; Espinosa-Zaragoza, Saúl (Ecosistemas y Recursos Agropecuarios, 2019)
A greenhouse experiment was conducted to identify the influence of endomycorrhizal fungi on the growth of Tabebuia donnell-smithiiRose. We used collections of endomycorrhizal fungi from Tenampulco, Puebla and San Rafael, Veracruz and the reference fungus Rhizophagus intraradices, which were evaluated with eutric fluvisol soil in combination with sand (1:1 v/v), peat moss (0.80:0.20 v/v) and bovine manure (0.80:0.20 v/v); 5-kg plastic bags were filled with the substrates. Nine treatments were evaluated with the combination of substrates and fungi, under a completely randomized design with four replicates. Morphological, physiological, root colonization and phosphorus content variables were determined in plant tissue 112 days after sowing (das). Results indicate a 121% increase in total biomass in the substrate with soil plus bovine manure added. Among microorganisms, R. intraradicesincreased biomass by 10.8 and 6.0% in relation to the snail and San Rafael collections, respectively. Biofertilization with R. intraradicespromoted stem and leaf area growth, and with the snail isolates, height and leaf area.  The highest phosphorus content compared to plants with native endomycorrhizal isolates occurred with R. intraradices.